Legal enforcement of individual behavior in the context of environmental policy - Daryanti; Sudarwanto, Albertus Sentot (Indonesian Journal of Social Sciences, 2024)
Awareness of environmental damage that affects the quality of human life, such as the adverse effects of climate change, requires action and intervention by the government and society through policy and law enforcement. Normatively, this research examines the relationship of law as a representation of social control or what is called law as a tool of social engineering to community behavior. Environmental law plays a role in maintaining and controlling damage arising from human behavior and will in daily activities. The result of this study is that legal formation in increasing public awareness and concern in Indonesia towards environmental damage in mitigating and adapting to climate change is still not effective. That is evidence that the percentage of people who believe in environmental damage due to climate change in Indonesia is the lowest. This study concludes that there is a need for the most effective law enforcement to increase individual awareness of the impact of environmental damage on sustainable development.